The Antimicrobial Peptide Human Beta-Defensin-3 Is Induced by Platelet-Released Growth Factors in Primary Keratinocytes - Andreas Bayer; Justus Lammel; Mersedeh Tohidnezhad; Sebastian Lippross; Peter Behrendt; Tim Klüter; Thomas Pufe; Jochen Cremer; Holger Jahr; Franziska Rademacher; Regine Gläser; Jürgen Harder (Hindawi Limited, 2017)
Platelet-released growth factors (PRGF) and its related clinically used formulations (e.g., Vivostat Platelet-Rich Fibrin (PRF®)) contain a variety of chemokines, cytokines, and growth factors and are therefore used to support healing of chronic, hard-to-heal, or infected wounds. Human beta-defensin-3 (hBD-3) is an antimicrobial peptide inducibly expressed in human keratinocytes especially upon wounding. The potent antimicrobial activity of hBD-3 together with its wound closure-promoting activities suggests that hBD-3 may play a crucial role in wound healing. Therefore, we analyzed the influence of PRGF on hBD-3 expression in human primary keratinocytes in vitro. In addition, we investigated the influence of Vivostat PRF on hBD-3 expression in artificially generated human skin wounds in vivo. PRGF treatment of primary keratinocytes induced a significant, concentration- and time-dependent increase in hBD-3 gene expression which was partially mediated by the epidermal growth factor receptor (EGFR). In line with these cell culture data, in vivo experiments revealed an enhanced hBD-3 expression in experimentally produced human wounds after the treatment with Vivostat PRF. Thus, the induction of hBD-3 may contribute to the beneficial effects of thrombocyte concentrate lysates in the treatment of chronic or infected wounds.